Faktor Yang Mempengaruhi Pemanfaatan Buku Kesehatan Ibu Dan Anak (KIA) terhadap Kunjungan Kehamilan pada Ibu Hamil di Puskesmas Kwala Bekala Medan 2025 - Ester Simanullang (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2025)
The low level of knowledge and attitudes of mothers regarding the use of the KIA handbook is due to their suboptimal use. Many mothers view the KIA handbook as merely a record of routine checkups, thus failing to understand the information it contains. This study aims to identify factors influencing the utilization of the Maternal and Child Health (KIA) handbook among mothers with toddlers in the Kwala Bekala Community Health Center (Puskesmas), Medan, Johor, in 2025. The study used an observational analytical method with a cross-sectional approach. The sample consisted of 45 mothers of toddlers living in the area. The sampling technique used was multistage sampling, conducted in stages to obtain appropriate respondents. The results showed that 62.2% of the utilization of the KIA handbook was influenced by mothers' attitudes, particularly regarding the implementation of the immunization program for pregnant women. The more positive the mother's attitude toward immunization, the greater the support of her husband's involvement in the process. The direction of the relationship found in this study was positive. Several factors that may influence mothers' attitudes toward the use of the KIA handbook include the number of children (the majority have one child (51.1%), the mother's education level (the highest is elementary school level at 19.42%), and the mother's occupation (the most common being a housewife at 30.66%). The use of the KIA handbook is classified as good at 62.2%, and the mother's attitude toward immunization during pregnancy shows a positive attitude at 75.6%.